Line manager perspectives on workplace-based efforts to reduce sickness absence: a qualitative study - Lene Rasmussen; Maj Britt Dahl Nielsen; Anne Helene Garde; Jesper Kristiansen (International Journal of Qualitative Studies on Health & Well-Being)
Introduction The purpose of this study is to examine line manager perspectives on two workplace-based efforts to reduce sickness absence (uniform procedures for managing sickness absence and initiating preventive actions), two components from an intervention to reduce sickness absence in public sector workplaces in Denmark. Methods We performed 19 semi-structured interviews with line managers from four public sector workplaces. The interviews were analysed using thematic analysis (TA). Normalization Process Theory (NPT) was used as theoretical framework. Results Uniform sickness absence procedures are meaningful and provide clear expectations for line managers and employees about roles and responsibilities during sick leave. Line managers expressed a desire for flexibility in adjusting the procedures to the individual needs of the employees. They also reported a need for proactive preventive actions that prevent sickness absence from occurring in the first place. The line managers reported lacking competencies to ensure appropriate sick leave management and that their own well-being was often overlooked. Conclusion Future interventions should focus on improving the work environment instead of focusing solely on absenteeism. It is essential to consider the well-being of the line managers and provide adequate training, as this can affect their capability to ensure the well-being of, and reduce sickness absence, among their employees.